Presence of Hepatic Steatosis Does Not Increase the Risk of Hepatocellular Carcinoma in Patients With Chronic Hepatitis B Over Long Follow-Up. (May 2020) - Lim, Chong Teik; Goh, George Boon Bee; Li, Huihua; Lim, Tony Kiat-Hon; Leow, Wei Qiang; Wan, Wei Keat; Azhar, Rafay; Chow, Wan Cheng; Kumar, Rajneesh
Background: Chronic hepatitis B (CHB) infection and nonalcoholic fatty liver disease (NAFLD) are liver diseases which may lead to hepatocellular carcinoma (HCC) formation. Both disease entities have been attributed independently to increase risk of HCC development. While concomitant hepatic steatosis in patients with CHB are becoming more frequent in view of increasing NAFLD prevalence, there is no conclusive evidence linking presence of hepatic steatosis and increased HCC risk in patients with CHB infection. This study explores the association of hepatic steatosis among CHB-infected individuals in HCC development. Methods: This is a retrospective study on a cohort of patients with CHB who underwent liver biopsy between January 2000 and December 2014. They were stratified according to presence and severity of histologically proven hepatic steatosis and subsequently followed up to evaluate the association between hepatic steatosis and HCC development. Results: Among 289 patients with a median follow-up of 111.1 months, hepatic steatosis was present in 185 patients (64.0%). In all, 27 patients developed HCC on follow-up and 21 of them had hepatic steatosis. Univariate Cox analysis showed that age (hazard ratio [HR] = 1.08, 95% CI = 1.042-1.12), type 2 diabetes mellitus (T2DM) (HR = 4.00, 95% CI = 1.622-9.863), and Ishak score (HR = 1.221, 95% CI = 1.014-1.472) were associated with HCC development, whereas multivariate Cox analysis demonstrated that age and T2DM (HR = 2.69, 95% CI = 1.072-6.759) were significant risk factors for development of HCC. Conclusions: Concurrent hepatic steatosis in patients with CHB infection is not a risk factor for hepatocellular carcinoma formation.